2022
DOI: 10.3390/ijms23158713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity/Exercise on Oxidative Stress and Inflammation in Muscle and Vascular Aging

Abstract: Functional status is considered the main determinant of healthy aging. Impairment in skeletal muscle and the cardiovascular system, two interrelated systems, results in compromised functional status in aging. Increased oxidative stress and inflammation in older subjects constitute the background for skeletal muscle and cardiovascular system alterations. Aged skeletal muscle mass and strength impairment is related to anabolic resistance, mitochondrial dysfunction, increased oxidative stress and inflammation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 261 publications
2
43
1
Order By: Relevance
“…Inflammation plays a pivotal role in hypertension, as a large number of studies have already demonstrated that systemic inflammation levels of patients with hypertension are elevated, which are closely associated with arterial stiffness ( 4 ). Investigators also found that inhibition of inflammation can alleviate hypertension in animal models ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation plays a pivotal role in hypertension, as a large number of studies have already demonstrated that systemic inflammation levels of patients with hypertension are elevated, which are closely associated with arterial stiffness ( 4 ). Investigators also found that inhibition of inflammation can alleviate hypertension in animal models ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two components are mainly involved in the RBE in our study: (i) the first bout of strength exercise and (ii) the strength training. Regular physical training promotes anti-inflammatory and antioxidant responses [ 64 , 65 ], which additionally contribute to the RBE.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle fibrosis impairs muscle function and disrupts muscle regeneration [ 38 ]. Oxidative stress and inflammation act in a feedback loop, contributing to these pathologies [ 39 ].…”
Section: Aging Factors In Skeletal Muscle ( When You Are Ol...mentioning
confidence: 99%